(untitled) (Journal of the College of Languages (JCL), 2014)
Nathaniel Hawthorne is famous for his psychological and moral themes. He is also famous for using symbolism in presenting his poignant themes of sin and its consequences. This research paper studies the use of symbols in Hawthorne’s The House of Seven gables as an example of his general use of symbolism in his novels. The general pattern of Hawthorne’s symbolism is that he presents one major symbol that embodies the main idea, and supports it with a number of minor symbols that develop and elucidate it. In The House of the Seven Gables, the major symbol is the house itself, which stands for corruption, evil, and the injustice of the past. This symbol is supported by such secondary symbols as the heart, the fountain, the interchange of light and dark, and the human characters themselves.